2004
DOI: 10.1128/iai.72.8.4393-4400.2004
|View full text |Cite
|
Sign up to set email alerts
|

Potential Involvement of Gelatinases and Their Inhibitors inMannheimia haemolyticaPneumonia in Cattle

Abstract: Mannheimia haemolytica infection of the lower respiratory tract of cattle results in a bronchofibrinous pneumonia characterized by massive cellular influx and lung tissue remodeling and scarring. Since altered levels of gelatinases and their inhibitors have been detected in a variety of inflammatory conditions and are associated with tissue remodeling, we examined the presence of gelatinases in lesional and nonlesional lung tissue obtained from calves experimentally infected with M. haemolytica. Lesional tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 62 publications
3
26
0
Order By: Relevance
“…Calf bronchopneumonia is characterized by massive cellular infl ux and lung tissue remodeling and matrix metalloproteases have been studied as key factors in tissue remodeling. Thus, increased concentration and activity of gelatinases (MMP2 and MM9) were detected in lung lesion of calves with experimentally induced M. haemolytica pneumonia [4] and in tracheobronchial lavage fl uid of calves with concurrent infections of P. multocida and M. bovirhinis [49]. Hinds et al [30] using intravenous application of E. coli lipopolysaccharide as a model for acute phase protein responses showed that covalent MMP-9 haptoglobin complex (Hp-MMP-9) was detected in the serum before and declined more rapidly than other acute phase proteins, and assumed that Hp-MMP9 complex can be early and accurate markers of calf respiratory diseases.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Calf bronchopneumonia is characterized by massive cellular infl ux and lung tissue remodeling and matrix metalloproteases have been studied as key factors in tissue remodeling. Thus, increased concentration and activity of gelatinases (MMP2 and MM9) were detected in lung lesion of calves with experimentally induced M. haemolytica pneumonia [4] and in tracheobronchial lavage fl uid of calves with concurrent infections of P. multocida and M. bovirhinis [49]. Hinds et al [30] using intravenous application of E. coli lipopolysaccharide as a model for acute phase protein responses showed that covalent MMP-9 haptoglobin complex (Hp-MMP-9) was detected in the serum before and declined more rapidly than other acute phase proteins, and assumed that Hp-MMP9 complex can be early and accurate markers of calf respiratory diseases.…”
Section: Discussionmentioning
confidence: 91%
“…Even nowadays the diagnosis of calf bronchopneumonia is based mostly on clinical observation. Isolation of causative microbiological agents and hematological, biochemical, and immunological analyses have been widely applied in epidemiological surveys and basic and applied research of the disease pathogenesis [2][3][4][5][6][7][8][9][10][11]. Most of these methods are available for veterinary practice; however, they are extremely rarely, if at all, used for the diagnosis of calf bronchopneumonia.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated levels of myeloperoxidase, elastase, alkaline phosphatase and nitric oxide activity, which are all known to contribute to lung injury, were found in neutrophils of heifers with respiratory tract infections (Wessely-Szponder et al, 2004). Matrix metalloproteinases (MMPs), especially gelatinases, released from neutrophil tertiary granules have been implicated in tissue damage and have been found produced by neutrophils that were isolated from lung lesions and exposed to M. (Pasteurella) haemolytica products (Starr et al, 2004).…”
Section: The Neutrophil Paradox and Bovine Respiratory Disease Complexmentioning
confidence: 99%
“…MMP 9 is a collagenase belonging to the gelatinase B group [ 5 ]. The gelatinase B group is a family of MMP’s that are zinc dependent proteinases capable of degrading at least one component of the extracellular matrix or basement membrane.…”
Section: Introductionmentioning
confidence: 99%
“…This capability assists in the migration of white blood cells, mostly neutrophils, from the blood to the site of inflammation [ 4 ]. MMP 9 is stored in tertiary granules within the bovine neutrophils and is released when neutrophil degranulation is induced by either chemical or microbial stimuli [ 1 , 5 , 10 , 11 ]. After release, MMP 9 is able to cleave interleukin 8, if present in the microenvironment into active interleukin 8.…”
Section: Introductionmentioning
confidence: 99%